1993
DOI: 10.1128/aem.59.12.4017-4023.1993
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquity of lignin-degrading peroxidases among various wood-degrading fungi

Abstract: Phanerochaete chrysosporium is rapidly becoming a model system for the study of lignin biodegradation. Numerous studies on the physiology, biochemistry, chemistry, and genetics of this system have been performed. However, P. chrysosporium is not the only fungus to have a lignin-degrading enzyme system. Many other ligninolytic species of fungi, as well as other distantly related organisms which are known to produce lignin peroxidases, are described in this paper. In this study, we demonstrated the presence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
9

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(85 citation statements)
references
References 51 publications
1
75
0
9
Order By: Relevance
“…It is interesting that the identity between the peroxidase MnPL and the MnP isoenzymes of P. chrysosporium (55%) is lower than found with the LiP of the same fungus (60% and 58% with isoenzymes H2 and H8 respectively). This could justify the reaction of P. eryngii peroxidases with antibodies against P. chrysosporium LiP reported by Orth et al (1993). However, differences between P. eryngii and P. chrysosporium peroxidase genes were shown by the lack of hybridization of P. chrysosporium DNA with a probe including a P. eryngii peroxidase gene compared with cross-hybridization between P. eryngii and P. ostreatus (Sarkar et al, 1997).…”
Section: Comparison With Other Fungal Peroxidasesmentioning
confidence: 95%
“…It is interesting that the identity between the peroxidase MnPL and the MnP isoenzymes of P. chrysosporium (55%) is lower than found with the LiP of the same fungus (60% and 58% with isoenzymes H2 and H8 respectively). This could justify the reaction of P. eryngii peroxidases with antibodies against P. chrysosporium LiP reported by Orth et al (1993). However, differences between P. eryngii and P. chrysosporium peroxidase genes were shown by the lack of hybridization of P. chrysosporium DNA with a probe including a P. eryngii peroxidase gene compared with cross-hybridization between P. eryngii and P. ostreatus (Sarkar et al, 1997).…”
Section: Comparison With Other Fungal Peroxidasesmentioning
confidence: 95%
“…Recently a similar peroxidase was detected in B. adusta, a fungus selected for biodegradation of industrial dyes [8], together with LiP already described by Kimura et al [9]. Despite some reports suggesting LiP production by Pleurotus species [10,11], a typical LiP has not been found in this genus. Since the ability to oxidize aromatic compounds directly, i.e.…”
Section: Introductionmentioning
confidence: 93%
“…Nevertheless, dioxins tend to remain in the culture despite incubations as long as 1 month, even with Phanerochaete chrysosporium [1,2], a fungus frequently used in bioremediation studies. Previous studies [7,8] suggested the existence of several fungi more active than P. chrysosporium. We therefore anticipated that we would be able to ¢nd e¡ective dioxin-degrading fungi by screening a variety of isolates and natural samples.…”
Section: Introductionmentioning
confidence: 96%